Patients' Experiences With Care for Lung Cancer and Colorectal Cancer: Findings From the Cancer Care Outcomes Research and Surveillance Consortium - Ayanian, John Z. (American Society of Clinical Oncology, 2010)
PURPOSE: To assess patients' experiences with cancer care, ratings of their quality of care, and correlates of these assessments. PATIENTS AND METHODS: For 4,093 patients with lung cancer and 3,685 patients with colorectal cancer in multiple US regions and health care delivery systems, we conducted telephone surveys of patients or their surrogates in English, Spanish, or Chinese at 4 to 7 months after diagnosis. The surveys assessed ratings of the overall quality of cancer care and experiences with three domains of interpersonal care (physician communication, nursing care, and coordination and responsiveness of care). RESULTS: English-speaking Asian/Pacific Islander patients and Chinese-speaking patients and those in worse health reported significantly worse adjusted experiences with all three domains of interpersonal care, whereas white, black, and Hispanic patients reported generally similar experiences with interpersonal care. The overall quality of cancer care was rated as excellent by 44.4% of patients with lung cancer and 53.0% of patients with colorectal cancer, and these ratings were most strongly correlated with positive experiences with coordination and responsiveness of care (Spearman rank coefficients of 0.49 and 0.42 for lung and colorectal cancer, respectively). After multivariate adjustment, excellent ratings were less common for each cancer among black patients, English-speaking Asian/Pacific Islander patients, Chinese-speaking patients, and patients reporting worse health status (all P ≤ .05). CONCLUSION: Patients' reports and ratings of care differed significantly by race, language, and health status. Efforts to improve patients' experiences with cancer care should focus on problems affecting Asian and Pacific Islander patients and those in worse health.